Justice in immigration - Miller, D (SAGE Publications, 2015)
Legitimate states have a general right to control their borders and decide who to admit as future citizens. Such decisions, however, are constrained by principles of justice. But which principles? To answer this we have to analyse the multifaceted relationships that may hold between states and prospective immigrants, distinguishing on the one hand between those who are either inside or outside the state’s territory, and on the other between refugees, economic migrants and ‘particularity claimants’. The claims of refugees, stemming from their human rights, are powerful though limited in scope: they hold against eligible states generally rather than the specific one to which they apply for asylum. Economic migrants cannot claim a right to be admitted as such, but only a right to have legitimate selection criteria applied to them. Particularity claimants, such as those seeking redress for harms inflicted on them or reward for the services they have rendered to the state, must show why awarding a right to enter is the appropriate response to their claims. Finally, does justice enable us to establish admission priorities between these different categories of migrants?